Tingkat Kepuasan Penumpang Terhadap Pelayanan Lost And Found PT. Avia Citra Dirgantara di Bandar Udara Abdulrachman Saleh Malang Jawa Timur - Hangga Dwipa Yudha; Desiana Rachmawati (Jurnal Kajian dan Penelitian Umum, 2023)
Lost and found unit officers are the ones who most often receive complaints from passengers who have lost or damaged baggage. This is related to passenger satisfaction, so that the quality of service in lost and found units requires more attention from the ground handling company at the airport. The purpose of this study was to determine the level of passenger satisfaction and to determine the attributes of service quality in determining the level of passenger satisfaction with the lost and found unit of PT. Avia Citra Dirgantara at Abdulrachman Saleh Airport in Malang. Researchers used descriptive quantitative methods. This study uses descriptive analysis techniques. Data analysis used the passenger satisfaction index and importance performance analysis. The number of samples used is 100 respondents, the questionnaire is addressed to passengers who have used the lost and found unit services of PT. Avia Citra Dirgantara. The place of this research is Abdulrachman Saleh Airport, Malang, East Java. The results of the research show that the satisfaction level of users of the lost and found unit can be seen from the IKP score of 37% stating that they are very satisfied and 32% stating that they are satisfied with the performance or service of the lost and found unit. If seen from the indicator with a very satisfied percentage it shows on the Emphaty indicator which is 30% and satisfaction shows on the Responsiveness indicator which is 63%. Attributes that need to be improved are located in quadrant I and there are 4 attributes in quadrant I.